2020
DOI: 10.3389/fpsyg.2020.01616
|View full text |Cite
|
Sign up to set email alerts
|

Stop Thinking: An Experience Sampling Study on Suppressing Distractive Thoughts at Work

Abstract: In modern work environments, it can be difficult for workers to avoid becoming distracted from their current task. This study investigates person-situation interactions to predict thought control activities (kind of self-control), which aim to stop distracting thoughts that enter the mind. Specifically, it was examined (1) how challenging work demands (time pressure, task complexity) activate workers' thought control to stop distractive thoughts (n level2 = 143) and relate to the effort to do so (n level2 = 91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…In contrast, individuals with higher suppression abilities did not. Niessen et al (2020) also conducted an experience sampling study combined with a laboratory task to assess the ability to suppress the unwanted thoughts of 158 workers. The workers engaged more often and more intensively in thought control activities at a moderate level of time pressure but only when they had a higher general ability to suppress unwanted thoughts.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, individuals with higher suppression abilities did not. Niessen et al (2020) also conducted an experience sampling study combined with a laboratory task to assess the ability to suppress the unwanted thoughts of 158 workers. The workers engaged more often and more intensively in thought control activities at a moderate level of time pressure but only when they had a higher general ability to suppress unwanted thoughts.…”
Section: Resultsmentioning
confidence: 99%
“…Dalam beberapa penelitian terdahulu, terapi ini hanya diaplikasikan pada kasus-kasus fobia rangsangan internal, merokok dan penyimpangan seksual. Terapi ini belum digunakan oleh tenaga kesehatan dalam mengatasi kecemasan pada pasien yang sedang mengalami sakit penyakit (Niessen et al, 2020;Parenteau & Lamontagne, 2021). padahal, terapi ini mampu meningkatkan suasana hati yang positif (Nørby, 2019).…”
Section: [Jurnal Kreativitas Pengabdian Kepada Masyarakat (Pkm) P-iss...unclassified
“…It has already been shown that person-situation interactions predict how people deal with too much information in the related field of thought control (Niessen et al, 2020a ). Building on these findings, we also assume that there are individual differences in the extent to which explanations support individuals' deletion of irrelevant files, trust in the AI system and finding the suggestions credible.…”
Section: Introductionmentioning
confidence: 99%